Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1088/1538-3873/128/968/104501
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Precise Radial Velocities from Near-infrared High-resolution Spectra of Low-mass Stars

Abstract: Given that low-mass stars have intrinsically low luminosities at optical wavelengths and a propensity for stellar activity, it is advantageous for radial velocity (RV) surveys of these objects to use near-infrared (NIR) wavelengths. In this work we describe and test a novel RV extraction pipeline dedicated to retrieving RVs from low mass stars using NIR spectra taken by the CSHELL spectrograph at the NASA Infrared Telescope Facility, where a methane isotopologue gas cell is used for wavelength calibration. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 77 publications
(138 reference statements)
2
44
0
Order By: Relevance
“…T g is our gas cell spectrum, obtained with a Fourier Transform Spectrometer (FTS) at the NASA Jet Propulsion Laboratory (JPL) at R~500,000 (Anglada-Escudé et al 2012;Plavchan et al 2013). Like Gao et al (2016), we find the gas cell optical depth τ g = 0.97 (vs. unity) because of the off-axis angle the gas cell was placed in the FTS, as opposed to CSHELL & iSHELL where the path length is minimized. T t (λ t ) corresponds to the Doppler shifted telluric absorption spectrum with optical depth τ t .…”
Section: Spectral Forward Modelsupporting
confidence: 60%
See 1 more Smart Citation
“…T g is our gas cell spectrum, obtained with a Fourier Transform Spectrometer (FTS) at the NASA Jet Propulsion Laboratory (JPL) at R~500,000 (Anglada-Escudé et al 2012;Plavchan et al 2013). Like Gao et al (2016), we find the gas cell optical depth τ g = 0.97 (vs. unity) because of the off-axis angle the gas cell was placed in the FTS, as opposed to CSHELL & iSHELL where the path length is minimized. T t (λ t ) corresponds to the Doppler shifted telluric absorption spectrum with optical depth τ t .…”
Section: Spectral Forward Modelsupporting
confidence: 60%
“…Known sources of external error arise from the fact that iSHELL is mounted at Cassegrain focus, and thus mechanically flexes as the telescope moves. Finally, iSHELL has both standard and non-standard fringing sources that will induce errors of > 10−20 ms −1 if not modeled sufficiently, and >50 ms −1 if not modeled at all (Gao et al 2016). Determining telluric induced error on RVs is the subject of a future investigation, but regions of large residuals are not found to be correlated with regions of high telluric absorption.…”
Section: Error Analysismentioning
confidence: 98%
“…c and 2d showed the similar peaks at 74.4 eV and 74.2 eV, respectively, which could be attributed to Al 2 O 3. It suggested that the film annealed at 800 °C had been fully oxidized and almost no nitride phases existed. Analysis of the binding energy from Si 2p peak, as shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Si doped TiN or TiAlN coatings could provide higher hardness, more excellent high oxidation resistance and better thermal stability owing to their special nc‐TiAlN/a‐Si 3 N 4 structure, which have attracted a broad attention . It is reported that both the dense amorphous Si 3 N 4 boundary phase and Al 2 O 3 top layer formed during high temperature annealing can act as barriers against oxygen diffusion along the grain boundaries and internally . TiAlSiN coating also exhibits better corrosion resistance than TiAlN coating because of the reduced crystal size and strain force caused by Si incorporation .…”
Section: Introductionmentioning
confidence: 99%
“…The work of Allende Prieto (2007) similarly foreshadowed aspects of our technique in terms of performing multiple pairwise comparisons, but their technique seeks only to improve RVs that have already been measured by some other technique. Our technique is also hardly the first to deliberately avoid using a synthetic template or template from a different star, and to favour instead using only the science observations themselves to construct a template; this approach has been taken elsewhere for both absorption cell spectrographs (Sato et al 2002;Johnson et al 2006;Gao et al 2016) and stabilized spectrographs (Anglada-Escudé & Butler 2012;Astudillo-Defru et al 2015;Zechmeister et al 2018), and has been demonstrated using both CCFs and ML (or least squares) approaches. HARPS-TERRA and SERVAL, which we used for RV extraction in Section 6.3, both adopt such a least-squares template matching approach.…”
Section: Conceptual Comparison With Existing Techniquesmentioning
confidence: 99%